The Network Coordination Office of NHERI (Natural Hazards Engineering Research Infrastructure) - Blain, Cheryl Ann; Bobet, Antonio; Browning, JoAnn; Edge, Billy L.; Holmes, William; Johnson, David R.; LaChance, Marti; Ramirez, Julio; Robertson, Ian; Smith, Tom; Thompson, Chris; Vielma, Karina; et al. (Frontiers in Built Environment, 2020)
NHERI, or the Natural Hazards Engineering Research Infrastructure, is supported by the United States National Science Foundation (NSF) as a distributed, multi-user national facility that provides the natural hazards research community with access to a powerful research infrastructure. NHERI is comprised of separate research infrastructure awards for a Network Coordination Office (NCO), Cyberinfrastructure, a Computational Modeling and Simulation Center, eight Experimental Facilities, and CONVERGE (an initiative to advance social sciences and interdisciplinary research). Awards made for NHERI contribute to NSF's role in the National Earthquake Hazards Reduction Program and the National Windstorm Impact Reduction Program of the United States. The mission of NHERI is to provide the earthquake, wind, coastal engineering, and social sciences communities with access to research infrastructure, education, and community outreach activities focused on improving the resilience and sustainability of the civil infrastructure against earthquakes, windstorms, and associated natural events such as tsunami and coastal storm surge. In this paper, the role and key NHERI activities are described for the NCO, which is led by Purdue University, along with partner institutions—the University of Texas at San Antonio, North Carolina State University, Texas Tech University, the U.S. Naval Research Laboratory, and the University of Hawaii at Manoa. The NHERI NCO serves as a focal point and leader of a multi-hazards research community, and maintains a community-based NHERI science plan. It manages scheduling of our partner NHERI Experimental Facilities and coordinates all components to ensure effective and fair governance, efficient testing and user support within a safe environment. Another important role of the NCO is to lead NHERI-wide educational and outreach activities. The NCO works to develop strategic national and international partnerships and to coordinate NHERI activities with other awardee components to form a cohesive and fully-integrated global natural hazards engineering research infrastructure that fosters collaboration in new ways.